Monitoring snowmelt at high temporal and spatial resolution: a method using standard digital camera images - Sold, Leo (Universität Tübingen, 2012)
The duration of snow cover and its hydrological and physical characteristics are crucial to High Arctic ecosystems. In this work terrestrial images taken via a standard digital camera are used to obtain information on the spatial and temporal variability of snow cover depletion in spring 2008. The research area Linnédalen is situated on about 78° northern latitude in western Spitsbergen, Svalbard. With respect to the relevant weather conditions and measurements on the snowpack the decline in snow covered area is analysed on a daily basis. The scope of this work is to contribute to a comprehensive image of the factors and processes controlling the timing and character of snow melt in the High Arctic. The strong linkage of snow cover to climatic conditions is particularly interesting in the context of Global Change. On the one side, changes in seasonal snow cover will directly aect the High Arctic ecosystem and on the other side the related change in surface albedo drives one of the most important feedback mechanisms in climate change. Die Dauer der Schneebedeckung sowie ihre hydrologischen und physikalischen Eigenschaften sind für arktische Ökosysteme von herausragender Bedeutung. In der vorliegenden Arbeit werden aus terrestrischen Aufnahmen einer Digitalkamera Informationen über die räumliche und zeitliche Variabilität der Schneeschmelze im Frühjahr 2008 gewonnen. Das Untersuchungsgebiet Linnédalen liegt auf etwa 78° nördlicher Breite inWestspitzbergen. Unter Berücksichtigung relevanterWetterdaten und Messungen an der Schneedecke wird die Veränderung der Schneebedeckung auf täglicher Basis ausgewertet. Ziel der Arbeit ist es, zu einem umfangreichen Verständnis der Faktoren und Prozesse beizutragen, die den Zeitpunkt und Ablauf der Schneeschmelze unter hocharktischen Bedingungen bestimmen. Die starke Abhängigkeit der Schneedecke von den klimatischen Gegebenheiten ist besonders in Hinblick auf eine zukünftige Änderung des Klimas interessant. Veränderungen wirken sich zum einen unmittelbar auf das Ökosystem aus und sind über die hohe Albedo der Schneedecke gleichzeitig zentraler Bestandteil des wohl wichtigsten Feedback-Mechanismus im Rahmen des Klimawandels.